Compensated transnational surrogacy in Australia: time for a comprehensive review. Issue 1 (18th January 2016) - Newson, Ainsley J
Summary: Commercial or compensated surrogacy involves providing payment for a woman to gestate a fetus to term and then hand over the child to commissioning parent(s). Compensated surrogacy is currently restricted by law or regulation in all Australian states and territories. New South Wales, Queensland and the Australian Capital Territory also restrict commissioning transnational compensated surrogacy, although there is evidence that this is not acting as a deterrent. Ethical issues arising in transnational compensated surrogacy include concerns relating to exploitation, commodification and welfare. The current status quo is unsatisfactory on legal, ethical and practical grounds. It is time to openly debate how Australia should balance the desire for childbearing through surrogacy with the limited domestic availability of women willing to act as surrogates.